2019
DOI: 10.1186/s40623-019-1073-z
|View full text |Cite
|
Sign up to set email alerts
|

Causes of the N–S compressional aftershocks of the E–W compressional 2008 Iwate–Miyagi Nairiku earthquake (M7.2) in the northeastern Japan arc

Abstract: In this study, we investigated the influence of local structural heterogeneities on aftershocks of the 2008 Iwate-Miyagi Nairiku earthquake (M 7.2) that occurred in the northeastern Japan arc. Although this area is characterized by an E-W compressional thrust faulting stress regime, many N-S compressional thrust-type and strike-slip-type earthquakes were also observed in the aftershock activity of the 2008 event. The occurrence of such N-S compressional aftershocks indicates that the differential stress was ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In and around many fault zones, Sibson (2020) found many geological and geophysical characteristics that support his "fault-valve" model, especially in compressional-transpressional tectonic regimes, which are better at containing overpressure and are 'load-strengthening' (mean stress rising with increasing shear stress). Maeda et al (2019) investigated the focal mechanisms of aftershocks of the 2008 Iwate-Miyagi Nairiku earthquake (M 7.2) in the northeastern Japan arc and detailed Vp/Vs structure there. They concluded that exceptional N-S compressional aftershocks occurred in regions with low strength due to the high pore pressure and with N-S compressional stress caused by the stress change due to the mainshock in a low differential stress regime.…”
mentioning
confidence: 99%
“…In and around many fault zones, Sibson (2020) found many geological and geophysical characteristics that support his "fault-valve" model, especially in compressional-transpressional tectonic regimes, which are better at containing overpressure and are 'load-strengthening' (mean stress rising with increasing shear stress). Maeda et al (2019) investigated the focal mechanisms of aftershocks of the 2008 Iwate-Miyagi Nairiku earthquake (M 7.2) in the northeastern Japan arc and detailed Vp/Vs structure there. They concluded that exceptional N-S compressional aftershocks occurred in regions with low strength due to the high pore pressure and with N-S compressional stress caused by the stress change due to the mainshock in a low differential stress regime.…”
mentioning
confidence: 99%